2009
DOI: 10.1039/b806400h
|View full text |Cite
|
Sign up to set email alerts
|

Approaching nanoscale oxides: models and theoretical methods

Abstract: This tutorial review deals with the rapidly developing area of modelling oxide materials at the nanoscale. Top-down and bottom-up modelling approaches and currently used theoretical methods are discussed with the help of a selection of case studies. We show that the critical oxide nanoparticle size required to be beyond the scale where every atom counts to where structural and chemical properties are essentially bulk-like (the scalable regime) strongly depends on the structural and chemical parameters of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
94
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(96 citation statements)
references
References 62 publications
2
94
0
Order By: Relevance
“…61 In these cases, the size of the particle is not large enough to build a Madelung field, which is an important component defining the stability of the structure of bulk polymorphs. Small (TiO 2 ) n (i.e.…”
Section: Tio 2 Nanoparticle Structurementioning
confidence: 99%
“…61 In these cases, the size of the particle is not large enough to build a Madelung field, which is an important component defining the stability of the structure of bulk polymorphs. Small (TiO 2 ) n (i.e.…”
Section: Tio 2 Nanoparticle Structurementioning
confidence: 99%
“…Where do we stand in the fabrication, understanding, and implementation of oxide nanomaterials? There is no doubt that overwhelming breakthroughs in oxide nanochemistry have been achieved [8] and it is impossible to fully appreciate them all within a single Review. Therefore, we provide a survey of selected exemplary works that outline the progress in research on oxide nanomaterials covering the period since 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, a number of theoretical calculations on MgO nanoclusters have been performed [12−15] since MgO is often considered as a prototype of ionic oxides. It has been demonstrated that the cubic rock-salt model can be applied to MgO nanoclusters when going beyond the size range of ~50 atoms [15]. However, most of the MgO clusters investigated previously are stoichiometric ones with an even number of atoms [12−15], and, to our knowledge, the electronic structure of the "cubic nonstoichiometric" clusters, i.e., cubic clusters consisting of an odd number of atoms, has not been theoretically examined.…”
mentioning
confidence: 99%